The Influence of the Inquiry Learning Model on Students' Interest in Learning and Social Studies Learning Outcomes Class IV SDN Were'a - Sutoyo; Lukman; Mahfud M Gamar (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Study This aim For explain the influence of the Inquiry Learning model on interest learning and results learn social studies students Class IV SDN Were'a . Types of research This is study quantitative use analysis descriptive . Research design using one-group pretest-posttest design and subjects study is participant educate class VI at SDN Were'a year lesson 2023/2024. Based on results study can concluded that the use of the Inquiry learning learning model is influential to interest and results learn social studies participants educate class IV ware'e shown​ from : (1) the Wilcoxon test results show positive ranks between interest learning social studies experience enhancement mark from pretest to posttest. The mean rank is 5.00 while the sum of ranks is 45.00; Paired Sample T Test results show calculated t value is 12.421 > from t table 2.262 then Ho is rejected and Ha is accepted which means There is influence use Inquiry Learning method with interest learning social studies in students class IV ware'e .; and result analysis regression shows the calculated t value is 4.290 > t table 2.364 then ha is accepted and ho is rejected and the R Square value is 0.76324 meaning the influence of X on Y is 76% , meanwhile the rest influenced by other variables that are not researched . Referring to the hypothesis above so can concluded the use of the Inquiry Learning model is influential to interest study and (2) positive Wilcoxon test results between ranks results learning social studies experience enhancement mark from pretest to posttest. Meank rank is 5.50 while the sum of ranks is 45.00; Based on the t table, the t table is 2.262. Because the calculated t value is 17,881 > t table 2.262 , Ho is rejected and Ha is accepted It means There is influence use method Learning Inquiry with results learning social studies in students class IV waree ; and based on results analysis regression Calculated t value based on the coefficient table of 4.747 > t table 2.364 then Ha is accepted and Ho is rejected and the R Square value is 0.763 meaning the influence of X on Y is 76% , meanwhile the rest influenced by other variables that are not researched .